2017
DOI: 10.7754/clin.lab.2017.170108
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of MicroRNAs in Calcific Aortic Stenosis

Abstract: MiR-26a, miR-939, and miR-374b* expression was decreased and miR-214 was increased in the calcified aortic valves of CAS patients. miR-214 may promote aortic valve calcification by repressing TWIST1 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Our hub genes and cross-linked miRNAs results in Table 2 also demonstrated that miRNA-199b-5p may directly target ACTN2 and ANK2 genes which are both suppressed in CAVS, suggesting the effects of these molecules on the pathogenesis of aortic stenosis. In addition, miRNA-374b [49], miRNA-340 [50] and miRNA-203 [51] have also been reported to be abnormally expressed in aortic stenosis patients, which can be used as a diagnostic/ prognostic biomarker of CAVS in the future. However, during the process of the disease, genetic alteration may occur secondary to some pathological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Our hub genes and cross-linked miRNAs results in Table 2 also demonstrated that miRNA-199b-5p may directly target ACTN2 and ANK2 genes which are both suppressed in CAVS, suggesting the effects of these molecules on the pathogenesis of aortic stenosis. In addition, miRNA-374b [49], miRNA-340 [50] and miRNA-203 [51] have also been reported to be abnormally expressed in aortic stenosis patients, which can be used as a diagnostic/ prognostic biomarker of CAVS in the future. However, during the process of the disease, genetic alteration may occur secondary to some pathological changes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their potential as therapeutic targets, those miRNAs that have been found to be functionally involved in BAV disease and morphology [ 142 ] should be further screened in BAV aortopathy (and controls) tissue and plasma/serum samples (including their extracellular vesicles components) to gain evidence of their potential as diagnostic and prognostic biomarkers.…”
Section: The Role Of Micrornasmentioning
confidence: 99%
“…Later, in a comparison between valves of healthy controls and patients with calcific aortic stenosis, miR-214 was increased in CAVD patients and osteocalcin, osteopontin, Runx2, and osterix were identified and validated as its targets. 41 Furthermore, in excised AVs from patients with CAVD, increased miR-214 expression was found to play a role in suppressing the apoptosis repressor with caspase recruitment domain ARC. 42 In addition, it was demonstrated that miR-214 stimulates the formation of calcific nodules in haVICs in vitro via the MyD88/NF-ĪŗB inflammatory pathway.…”
Section: Resultsmentioning
confidence: 98%